PRONOUNS AND THEIR PLACE IN ARABIC GRAMMAR - Nuriddinov Khozhiakbar (Web of Journals Publishing, 2024)
In Arabic, the pronoun belongs to the group of nouns and is divided into the types damir munfasila, ismi ishara, damir fasl, damir muttasila, damir a'aid, ismi mawsula, ismi istifhom.
Keywords: Person, number, genus, gender, concord, declension.